Dimensions of Protection Against Deceitful Trade Competition in the Protection of Geographical Indications (Fakultas Hukum Universitas Hang Tuah, 2022)
The dimension of Geographical Indications protection is not only intended to provide protection to consumers, but is actually also a protection for business actors who own registered Geographical Indications. Competition in the increasingly fierce business creates dishonest business actors who claim to have products of the same quality as registered Geographical Indications. The existence of geographical indication rights as communal rights contains a stronger defense dimension than individual rights. Together and institutionally, the geographical indication rights holder community can design strategic steps to fight this unfair competition. Local governments play a key role in protecting and handling registered Geographical Indications in their regions